Contre l'indifférence des privilégiés : à quoi sert le care - Gilligan, Carole; Hochschild, Arlie; Tronto, Joan (Payot, 2013)
Comment résister à l'injustice ? Peut-on vaincre le " capitalisme émotionnel " ? Une éthique du care globale est-elle possible à l'heure des migrations transnationales ? Réunies pour la première fois, trois féministes et pionnières de la théorie et de l'éthique du care, la psychologue Carol Gilligan, la sociologue Arlie Hochschild et la politiste Joan Tronto, apportent leurs éléments de réponse avec, en ligne de mire, une injonction : encourager chacun à prendre ses responsabilités pour agir contre l'indifférence des privilégiés. Un événement intellectuel.
Keywords: approches et analyses; care; discipline; division sexuelle du travail; genre; patriarcat; privilèges; psychologie; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; éthique

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences